A high-performance linear motor drive for robotics - Ng, Jeremy Yi Long (Nanyang Technological University, 2024)
Permanent Magnet Linear Motors have been gaining popularity in a variety of sectors and applications due to their excellent performance, energy efficiency, compact design, maintenance-free operation, and wide range of operations. The dimensions and sizing of the Permanent Magnet Linear Motor for robotics will be modeled similarly to real-world linear motors for robotics for this project. Factors such as split ratio, size, pole pitch, and so on will be examined further. This study will present the design process utilizing the simulation software JMAG-Designer. The design decisions, problems, and observations will be made in this part. The purpose of this research is to try and improve the performance of the Permanent Magnet Linear Motor for robotics. Based on calculations and trial and error from the first model design, analysis and changes will be made.